A comparative business efficacy analysis between private and public-sector construction business operating units - Chwene, Molefi C. (North-West University (South Africa), 2018)
The public-sector business strategies at DWS Construction are analysed with an intension to highlight mechanisms that can potentially improve the current business operating model of DWS Construction. The study determines a framework that may influence the efficacy and sustainability of the public-sector construction business unit operating in an environment which is dominated by the private sector businesses. A distinctive relation on similarities based on public and private sector business are drawn to provide possible alternative solutions to the prevailing business administration performance shortcomings at DWS Construction, and to any other similar public-sector business. This is meant to address poor service delivery, low efficacy of public administrative business systems, financial management failures and poor audit outcomes as experienced across most public-sector institutions. A predetermined research sample comprising middle and senior managers who fall between level 11 and 14 according to the public-sector salary levels participated in this study, and the study follows qualitative data approach from these distinct groups selected based on their experience and knowledge of the private and public-sector construction industry. The study finds that DWS Construction is not positioned to operate optimally in the private sector dominant industry due to government bureaucracy and policy directives. Drastic changes to the current strategic architecture are required to corporatise DWS Construction.
MBA, North-West University, Mafikeng Campus, 2018
Keywords: Sustainability; public and private sector; business efficacy analysis; DWS Construction